Acute Unilateral Ptosis and Myositis Following the H1N1 Influenza Vaccine. Issue 1 (January 2020) - Basilious, Alfred; Jivraj, Imran; DeAngelis, Dan
Abstract : The authors present a rare case of sudden onset unilateral complete ptosis occurring hours after administration of the H1N1 influenza vaccine. A complete workup for autoimmune and neurological disease was negative. MRI of the orbits demonstrated unilateral orbital myositis involving the left superior rectus/levator complex, superior oblique, and medial rectus muscles. Ptosis resolved spontaneously over 2 months without intervention. An autoimmune mechanism may explain rare cases of orbital myositis following administration of the H1N1 influenza vaccination. A case of acute onset and spontaneous resolution of complete unilateral ptosis and orbital myositis post H1N1 influenza vaccination.